2019
DOI: 10.3889/oamjms.2019.758
|View full text |Cite
|
Sign up to set email alerts
|

Gambir Extract (Uncaria Gambir) Decreases Inflammatory Response and Increases Gastric Mucosal Integrity in Wistar Rats - Model Gastritis

Abstract: BACKGROUND: Uncaria gambir (local name: gambir) is a plant native to Sumatera, Malaya and Borneo. This plant is potential as local wisdom for therapeutics. In Sumatera, gambir was used as a traditional treatment for fever, diarrhoea, diabetics and wound healing. AIM: To explore the efficacy of gambir extract on TNF alpha level, prostaglandin E2 level, lesson area, body weight, lipid profile and leptin level in Wistar rat-model gastritis. METHODS: This study was an experimental study, with a pre-pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…14 In dental practice, clove oil, gambir, jatropha, sidaguri and bee venom have been usually used to relieve dental pain by applying them directly to the affected tooth. [4][5][6][7] A preliminary in vitro study in an animal model with periapical lesion showed that the root of sidaguri was able to decrease C-reactive protein level (CRP), one of many molecules that take part in the acute inflammatory process. 8 Another study showed that root of sidaguri was a non-selective COX inhibitor, an enzyme involved in the synthesis of prostaglandin E2.…”
Section: Discussionmentioning
confidence: 99%
“…14 In dental practice, clove oil, gambir, jatropha, sidaguri and bee venom have been usually used to relieve dental pain by applying them directly to the affected tooth. [4][5][6][7] A preliminary in vitro study in an animal model with periapical lesion showed that the root of sidaguri was able to decrease C-reactive protein level (CRP), one of many molecules that take part in the acute inflammatory process. 8 Another study showed that root of sidaguri was a non-selective COX inhibitor, an enzyme involved in the synthesis of prostaglandin E2.…”
Section: Discussionmentioning
confidence: 99%
“…is an Indonesian plant that contains flavonoids, especially catechins (40%-80% of the dry extract weight), procyanidin B1, procyanidin B3, and gambirin (1%), and (-)-epicatechin (1.5%). Gambir is reported to have antibacterial, antiseptic, antioxidant, and antiinflammatory properties (Dewi et al, 2018;Oswari et al, 2019;Melia et al, 2015;Ningsih and Rahayuningsih, 2019). In animal models of liver fibrosis using white rats (Rattus norvegicus L.) induced by the hepatotoxic compound carbon tetrachloride (CCl 4 ), the gambir extract showed potency as a hepatoprotector (Fahrudin et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported catechu from Uncaria gambir Roxb. It possesses antioxidant [ 11 ], anti-inflammatory [ 12 ], and antimicrobial activities [ 13 ]. Unsurprisingly, the aforementioned biological activities of catechu mainly result from catechin and epicatechin [ 14 ].…”
Section: Introductionmentioning
confidence: 99%